Post-cesarean colonic ileus: cecal perforation without mechanical obstruction - Cazabán, Luis A; Baldizán, Jorge W; Flores, Nelson H; Carriquiry, Luis A (Cirugía del Uruguay, 1976)
Two cases of important cecal distension due to colonic ileus following cesarean section are reportea. One of them with diastasic perforation of the cecum; the other one, with pre-perforative lesions of its wall. The authors analyze the available bibliography on this subject. The diagnostic problems are remarked and particular emphasis is placed on the fact that only an early laparotomy with a decompressive cecostomy can decrease the high mortality of this condition.